Pengaruh Convenience to The Customer dan Customer Perceived Value and Benefit Terhadap Impulse Buying - Harun Muhyiddin (Institute of Social and Political Science Jakarta (Institut Ilmu Sosial dan Ilmu Politik Jakarta - IISIP Jakarta), 2022)
This article reports the results of research on the Influence of Convenience to The Customer Factors and Customer Perceived Value and Benefit Factors on Impulse Buying in Online Retail: Berrybenka. The conceptual and theoretical basis used is about the internal factors in consumers that affect impulsive buying behavior. The research method is quantitative, survey, with primary data originating from questionnaires distributed to 100 people using convenience sampling, while secondary data comes from various books and relevant research results. The results showed that the internal factors that influence consumers’ impulsive buying behavior are search convenience, transaction convenience, and hedonic. However, the factors of access convenience, evaluation convenience, post-purchase and utilitarian, did not show any effect on impulsive buying behavior.